Competing and decisive roles of 1D/2D/3D sp2-carbons in controlling the shape switching, contact sliding, and functional properties of polymers. (September 2022) - Vishwakarma, J.; Jaiswal, S.; Bharti, P.; Dhand, C.; Kumar, R.; Hashmi, S.A.R.; Srivastava, A.K.; Dwivedi, N.
Abstract: Stimuli-controllable shape-shifting polymers, such as shape memory polyurethane (SMPU), are promising for robotics, aerospace, sensing, automobiles, and many other applications. However, slow actuation or high shape recovery time, low recovery stress, and inadequate understanding of friction and wear characteristics of SMPU limit its widespread practical uses. Further, SMPU has been engineered with diverse foreign materials but inconsistent results and ambiguous underlying mechanisms, especially when SMPU is modified with sp 2 -carbon materials, are also major concerns. Here we determine and simultaneously cross-compare the role of 1D/2D/3D graphitic carbons, namely carbon nanotubes, multilayer graphene and graphite, in controlling the properties of SMPU. The designed SMPU-composites display 8–15-folds faster shape recovery in different mediums, higher recoverable stress, faster healing of the dents, 2–3-folds lower friction, better wear resistance, and improved thermal, wettability, and dielectric properties than pristine SMPU. Further, while the introduction of 2D/3D graphitic carbons massively degrade the elongation, 1D carbon nanotubes maintains the stretchability of SMPU. Eventually, we develop a novel heat alarm device employing SMPU-composite as a major component that acts as a heat sensor, an actuator, and enables the closure of the circuit. Our results uncover many unknown phenomena of engineered SMPU and pave the way for the development of smart-technologies. Highlights: Engineering of shape memory polyurethane (SMPU) via multi-dimensional graphitic sp 2 carbons. Reinforcement of multi-dimensional graphitic sp 2 carbons enables 8–15-fold faster shape recovery in SMPU. Reinforcement of multi-dimensional graphitic sp 2 carbons enhances the recovery stress of SMPU. Reinforcement of multi-dimensional graphitic sp 2 carbons decreases the friction and wear of SMPU. The development of heat alarm device, employing engineered SMPU as a major component, is demonstrated.